An Integrated Web System for National Indonesian Number (NIK) Based Zakat Eligibility Verification Geospatial Mustahik Mapping - Gio Vani Jefri; Ahmad Hafizon; Aini Qolbiyah; Arif Rahman Hakim; Adri Daswin (Journal of Education Research, 2026)
Inefficiencies in zakat management, particularly in eligibility verification and beneficiary distribution, remain a critical challenge due to fragmented data and manual processes. Existing systems rarely integrate identity-based verification with spatial analysis, resulting in delays, inaccuracies, and limited transparency. This study aims to develop and evaluate an integrated web-based zakat system featuring NIK-based eligibility verification and geospatial mustahik mapping to improve the management of Zakat Al-Mihnah. Using an Agile development approach, the system was iteratively designed based on user requirements identified through observation and literature review. The results demonstrate that the proposed system enhances data accuracy, accelerates verification processes, and improves the efficiency and transparency of zakat distribution. In addition, geospatial mapping enables more targeted and equitable allocation of funds. These findings highlight the system’s potential as a scalable digital solution for strengthening accountability and decision-making in zakat management, while contributing to the advancement of technology-driven Islamic social finance systems.